Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/nsmb987
|View full text |Cite
|
Sign up to set email alerts
|

Sec15 interacts with Rab11 via a novel domain and affects Rab11 localization in vivo

Abstract: Sec15, a component of the exocyst, recognizes vesicle-associated Rab GTPases, helps target transport vesicles to the budding sites in yeast and is thought to recruit other exocyst proteins. Here we report the characterization of a 35-kDa fragment that comprises most of the C-terminal half of Drosophila melanogaster Sec15. This C-terminal domain was found to bind a subset of Rab GTPases, especially Rab11, in a GTP-dependent manner. We also provide evidence that in fly photoreceptors Sec15 colocalizes with Rab11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
234
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(246 citation statements)
references
References 45 publications
11
234
0
1
Order By: Relevance
“…A previous study on MDCK cells suggested that the exocyst, through its Sec15 component, may function as a Rab11 effector to regulate basolateral-to-apical transcytosis (23). The sec15 mutant in the fly photoreceptor results in strong accumulation of Rab11 within the apical membranes of the photoreceptor (22). We confirmed the accumulation of RAB-11-positive vesicles at the apical PM in sec-10 mutants (Fig.…”
Section: Dual Involvement Of Sec-10 In Apical and Basolateral Endosomalsupporting
confidence: 76%
See 2 more Smart Citations
“…A previous study on MDCK cells suggested that the exocyst, through its Sec15 component, may function as a Rab11 effector to regulate basolateral-to-apical transcytosis (23). The sec15 mutant in the fly photoreceptor results in strong accumulation of Rab11 within the apical membranes of the photoreceptor (22). We confirmed the accumulation of RAB-11-positive vesicles at the apical PM in sec-10 mutants (Fig.…”
Section: Dual Involvement Of Sec-10 In Apical and Basolateral Endosomalsupporting
confidence: 76%
“…Consistent with this idea, the exocyst localizes to the PM where exocytosis actively occurs and has been implicated in many cellular trafficking processes including polarized budding in yeast (14), neurite growth in neurons (15), GLUT4 membrane insertion in fat cells (16), and cell migration (17)(18)(19). Recent studies have revealed an association between the exocyst and recycling endosome-localized proteins, such as Arf6 (20), AP1B (21), and Rab11 (22), and the presence of exocyst on multiple populations of endosomes (23). Interfering with exocyst functions affects several endocytic pathways, such as transferrin receptor (TfR) recycling in nonpolarized cells (20), and apical and basolateral recycling in polarized cells (23,24).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Through this interaction, Sec4 controls the assembly of the exocyst complex that is needed for the tethering of secretory vesicles at the plasma membrane. In other eukaryotes, Rab proteins such as Rab11 and Rab8, which are implicated in membrane trafficking to the plasma membrane, were also shown to interact with Sec15 (Zhang et al 2004;Wu et al 2005;Oztan et al 2007). Together, these studies suggest that the exocyst functions as a downstream effector of Rab proteins to mediate vesicle tethering at the plasma membrane in eukaryotic cells.…”
Section: The Rab Family Of Small Gtp-binding Proteinsmentioning
confidence: 69%
“…We found that the Sec15 subunit is polarized during cell migration. Because Sec15 is a Rab11 binding protein (15,16), we tested further the relationship between these two proteins. We found that Sec15 polarity is controlled by rab11 activity and that sec15 and other subunits of the exocyst are necessary for the spatial restriction of RTK activity and for border cell migration.…”
mentioning
confidence: 99%